Facts about Zinc - Linda B. Bobroff (EDIS)
Revised! FCS-8705, a 2-page fact sheet by Linda B. Bobroff, uses a question and answer format to informs clients about this mineral for human nutrition. Published by the UF Department of Family Youth and Community Sciences, June 2009.